pH dan Suhu Optimum Aktivitas Enzim Amilase Kapang Termofilik dari Hot Spring Sulili - Indrayani, Indrayani; Hambali, Amiruddin; Jusran, Jusran; Putra, Reski Praja (Agricultural Technology Education Study Program, 2024)
Enzyme activity is greatly influenced by several factors including incubation time, temperature, and pH. This study aimed to determine the optimum pH and temperature of amylase enzyme activity of mold PSA 02 (5) isolated from Sulili hot spring, Pinrang Regency, South Sulawesi, Indonesia. This study was conducted in two stages, the first is determining the optimum pH of amylase enzyme activity where enzyme activity testing carried out at pH 4, 5, 6, 7, and 8. After determination of optimum pH, it continued to determine the optimum temperature of amylase enzyme activity at temperatures of 30, 40, 50, 60, 70, and 80oC. Determination of protein content using the Lowry method and determination of amylase enzyme activity using the Dinitrosalicilyc (DNS) method. The results of this study showed that the optimum pH of amylase enzyme activity is pH 4 with an enzyme activity value of 81.37 U/mL and a specific enzyme activity of 57.61 U/mg, while the optimum temperature of amylase enzyme activity is 50oC with a value of 81.44 U/mL and a specific enzyme activity of 57.74 U/mg. It is interesting to note that the amylase enzyme activity remains high up to a temperature of 80oC with a value of 81.20 U/mL. This study indicates that the amylase enzyme of mold isolate PSA 02 (5) is a thermostable enzyme up to a temperature of 80oC.